2012
DOI: 10.1556/jba.1.2012.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Beyond description: Understanding gender differences in problem gambling

Abstract: Background and aims: Though women make up roughly one third of all problem gamblers, research has typically focused on male problem gamblers. Recent research has started to shift its attention toward the importance of gender. However, studies rarely attempt to understand gender differences in problem gambling or subject these differences to thorough multivariate analyses. To address some of the gaps in our knowledge of gender differences, we examine whether patterns of gambling behavior and psychological facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…Instead, the findings of this study supported the findings of gender-specific motivation to gamble from many previous studies [12,14]. Women gamblers in this study used gambling as a way to avoid stress, to relieve boredom, or to escape from feeling lonely.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Instead, the findings of this study supported the findings of gender-specific motivation to gamble from many previous studies [12,14]. Women gamblers in this study used gambling as a way to avoid stress, to relieve boredom, or to escape from feeling lonely.…”
Section: Discussionsupporting
confidence: 87%
“…Many previous studies have reported that gambling behaviors and gambling etiology appear to be different between men and women problem gamblers [11][12][13][14][15]. No single explanation can be applied to gender differences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the internet is changing gambling opportunities rapidly and recent data are needed to investigate the prevalence of internet gambling and the risk associated for both men and women. Finally, gender differences in gambling prevalence have been associated with differences in types of games and patterns of gambling (Potenza et al, 2001;Stark, Zahlan, Albanese, & Tepperman, 2012), suggesting that investigating specific gambling activities may prove critical in understanding gender differences in gambling.…”
mentioning
confidence: 99%
“…This result is comparable to other studies in the field (Chevalier 2008;Marshall and Wynne 2003;Afifi et al 2010). On the other hand, some national and provincial studies report that men are more likely to be problem gamblers (Kairouz et al 2011;Stark et al 2012).…”
Section: Discussionmentioning
confidence: 99%